Measuring two-dimensional heat flux using a plate sensor and infrared thermography - Matthew J. DiDomizio; Parham Dehghani (MethodsX)
The thin-skin calorimeter sensor is used to measure heat flux. This device is limited to measurements at a single physical location. A new method, denoted HFITS, has been developed to obtain heat flux measurements over a two-dimensional surface. A large flat plate sensor is positioned near a heat source at the location where field heat flux measurements are desired; exemplar plate sensor designs and property data are provided in this work to support method application. An infrared camera is used to measure the temperature of the plate sensor over time. Thermogram sequences are translated to a rectilinear grid, and a two-dimensional inverse heat transfer model is used to derive measurements of net heat flux to the plate sensor. Incident heat flux (consisting of both radiative and convective components) is calculated by applying numerical approximations, optimizations, and engineering correlations. A validation experiment was performed, and the HFITS method was shown to produce measurements consistent with Schmidt-Boelter heat flux gauges, having an RMSE of 0.5 kW m-2 for an incident radiative heat flux of 18 kW m-2 (< 3 %). Limitations of the method, such as response time, sensor survivability, noise, and measurement uncertainty, are detailed. • The HFITS method provides measurements of two-dimensional heat flux fields to a target location. • The plate sensor is simple to fabricate, inexpensive, and is practical to deploy in various thermal engineering applications. • Exemplar plate sensor designs, property data, and infrared camera considerations are provided to support method application.